Knee rotation in patients with and without patellofemoral instability and its correlation with patellar tendon trochlear groove distance - Himanshu Gupta; Vineet Jain; Nilansh Kataria; Ashish Dutt Upadhyay; Pallav Mishra; Himanshu Kataria (Journal of the Bulgarian Orthopaedics and Trauma Association)
Background and study aims: There are limited studies assessing the role of “knee rotation” in patellofemoral instability (PFI). Knee rotation is the external rotation of the proximal tibia with respect to distal femur. The study was performed to compare knee rotation, patellar tendon lateralisation and patellar tendon trochlear groove (PTTG) distance measured on MRI between patients with and without PFI and to assess the relative association of these factors with PFI.